Contributions of Asn2198, Met2199, and Phe2200 in the factor VIII C2 domain to cofactor activity, phospholipid-binding, and von Willebrand factor-binding - Lewis, Deborah A.; Pound, Mary L.; Ortel, Thomas L. (Thrombosis and Haemostasis, 2003)
The crystal structure of the factor VIII C2 domain consists of a β-sandwich core from which β-hairpins and loops extend to form a hydrophobic surface. The hydrophobic surface includes M2199 and F2200 at the tip of the 1st β-hairpin. To determine the individual contributions of residues N2198, M2199, and F2200 to phospholipid and von Willebrand factor (vWF) binding properties of factor VIII, we prepared mutant proteins with single alanine substitutions. We found that single mutations at N2198 and M2199 had relatively little impact on cofactor activity, or phospholipid and vWF binding. However the F2200A mutant had slightly lower cofactor activity at subsaturating phospholipid concentrations. Competitive ELISAs suggested that F2200 plays a more important role in both phospholipid-binding and vWF-binding than N2198 and M2199. All mutant proteins were still recognized by a monoclonal antibody and two factor VIII inhibitors that neutralized cofactor activity and blocked factor VIII binding to phospholipids.Presented in part at the XVIII Congress of the International Society on Thrombosis and Haemostasis, Paris, France, 6-12 July 2001, and the 43rd Annual Meeting of the American Society of Hematology, Orlando, Florida, 7-11 December 2001
Keywords: Factor VIII; ESH4; inhibitor; phospholipid-binding; von Willebrand factor